Effect of Dosage Reduction of Hypoglycemic Multidrug Regimens on the Incidences of Acute Glycemic Complications in People With Type 2 Diabetes Who Fast During Ramaḍān: A Randomized Controlled Trial - Zaghlol, Louay Y.; Beirat, Amir F.; Amarin, Justin Z.; Hassoun Al Najar, Amro M.; Hasan, Yazan Y.; Qtaishat, Abdallah; Tierney, Michael E.; Zaghlol, Raja Y.; Zayed, Ayman A. (Frontiers in Endocrinology, 2021)
Objective We aimed to investigate the effect of dosage reduction of four hypoglycemic multidrug regimens on the incidences of acute glycemic complications in people with type 2 diabetes who fast during Ramaḍān. Methods We conducted an open-label, parallel-group, randomized controlled trial at a tertiary care center in Amman, Jordan. We recruited adults with type 2 diabetes who expressed an intention to fast during Ramaḍān and were adherent to one of four regimens—namely: metformin and glimepiride; metformin and vildagliptin; metformin and insulin glargine U100; or, metformin, insulin glargine U100, and human regular insulin. We randomly assigned participants in a 2:1 ratio to low- or regular-dosage therapy. The primary outcomes were the incidences of hypoglycemia and hyperglycemia during the 29 days of Ramaḍān 2017, and the secondary outcomes were the incidences of diabetic ketoacidosis and hyperosmolar hyperglycemic state during the same period. Results We randomly assigned 687 participants to low-dosage therapy (n = 458) or regular-dosage therapy (n = 229) and included 678 (452 and 226, respectively) in the final analysis. The incidence of hypoglycemia was lower in the low-dosage group compared with the regular-dosage group (19 [4.2%] vs. 52 [23.0%], respectively; OR, 0.15 [95% CI, 0.08–0.26]; P < 0.001). The incidence of hyperglycemia did not differ between the low- and regular-dosage groups (319 [70.6%] vs. 154 [68.1%], respectively; OR, 1.12 [95% CI, 0.79–1.58]; P = 0.5). No participants experienced diabetic ketoacidosis or hyperosmolar hyperglycemic state. Each 1% decrease in the baseline HbA1c concentration was associated with a 19.9-fold (95% CI, 9.6–41.5; P < 0.001) increase in the odds of hypoglycemia, and each 1% increase in the baseline HbA1c concentration was associated with a 15.7-fold (95% CI, 10.0–24.6; P < 0.001) increase in the odds of hyperglycemia. Conclusion Dosage reduction decreases the incidence of hypoglycemia without a concomitant increase in the incidences of hyperglycemia, diabetic ketoacidosis, and hyperosmolar hyperglycemic state in people with type 2 diabetes who fast during Ramaḍān. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT04237493.